Technology-Enhanced Science Teaching for 21st-Century Learning: A Systematic Review of Evidence-Based Strategies and Their Alignment with SDG 4 - Sayadi, Darwisa; Pangandaman, Hamdoni (Universitas Negeri Semarang, 2025)
The evolving demands of 21st-century education require science teaching strategies that promote student engagement, critical thinking, and real-world application. Although many studies examine individual approaches, consolidated evidence identifying which strategies best align with modern educational outcomes—and what large-scale evidence from the fully online COVID-19 period implies—remains limited. This study systematically reviews and synthesizes high-quality empirical evidence on technology-enhanced strategies for teaching science, with a focus on their use in teacher education programs. Guided by the PICO framework, a comprehensive search across seven major databases (2015–2025) yielded 133,414 records. After applying predefined inclusion/exclusion criteria and conducting critical appraisal using the JBI checklists and ROBVIS, 23 studies met eligibility for analysis. Thematic synthesis revealed three dominant categories of effective strategies: (1) immersive technologies (e.g., augmented reality, virtual reality, interactive simulations); (2) collaborative digital platforms (e.g., Google Classroom, Edmodo, Internet Reciprocal Teaching); and (3) interactive learning tools (e.g., virtual laboratories, gamified slide presentations, digital flipbooks). Across diverse disciplines and grade levels, these strategies generally improved engagement, conceptual understanding, and scientific literacy under controlled or well-supported conditions. Triangulation with evidence from fully online learning during COVID-19, however, indicates heterogeneous—and at scale, often negative—system-level outcomes when enabling conditions are weak, as reflected in international assessments (e.g., PISA 2022). Distinct from prior reviews, this study integrates technology-enhanced pedagogy with SDG 4 goals, providing a global synthesis that bridges instructional innovation and sustainable education frameworks. The findings underscore the importance of professional development, curriculum alignment, and equitable technology access as enabling conditions for successful implementation. We conclude that student-centered, technology-enhanced approaches embedded within inquiry- or project-based frameworks can advance learning outcomes while supporting quality, inclusive, and future-ready science education.